Bangladesh-India Relations: Addressing the Border Killing ConcernsBangladesh-India Relations: Addressing the Border Killing Concerns - Mizanur Rahman (International Journal of Global Sustainable Research, 2024)
The relationship between Bangladesh and India is characterized by a complex interplay of historical, geographical, political, and socio-economic factors. Despite numerous shared interests and efforts to foster collaboration, one persistent cause that continues to strain this relationship is the incidence of border killings along the Bangladesh-India border.  Drawing upon a variety of primary and secondary sources, including official statements, reports, academic literature, and media coverage, this research examines the historical context and geopolitical dynamics that have contributed to the phenomenon of border killings between the two countries. It explores the role of factors such as border disputes, illegal migration, cross-border crime, and security concerns in exacerbating tensions and leading to violent confrontations along the border regions. It also investigates the responses and strategies employed by both governments to address the issue, including border management measures, bilateral agreements, and diplomatic initiatives.By shedding light on its causes, consequences, and potential remedies, it aims to inform policymakers, and the general public about the urgent need for concerted scholarly efforts to mitigate this longstanding challenge and foster greater mutual understanding and cooperation between the two neighboring nations.